Expression of the potential cancer stem cell markers CD133 and CD44 in medullary thyroid carcinoma: A ten‐year follow‐up and prognostic analysis. Issue 2 (12th January 2016) - Bi, Yalan; Meng, Yunxiao; Wu, Huanwen; Cui, Quancai; Luo, Yufeng; Xue, Xiaowei
Abstract : Background and Objectives: To investigate the expression profiles of cancer stem cells (CSCs) markers CD133 and CD44 in a cohort of medullary thyroid carcinoma (MTC) patients, and their prognostic values during 10‐year follow‐up. Methods: MTC samples were obtained for H&E and immunohistochemical analysis. Survival analysis was performed using Kaplan–Meier method and log‐rank test. Results: Both the CD133 and CD44 positives were higher in MTC than control. High expression of CD133 and CD44 was positively correlated with capsule invasion and each other, and their co‐expression was significantly correlated with capsule invasion, tissue invasion, and metastases at surgery. Tumor size, capsular invasion, tissue invasion, metastases at surgery, surgical plan, lymph node metastases, TNM stage, CD133, and CD44 were prognostic factors for overall survival (OS) and/or disease free survival (DFS). Both the CD133 and CD44 were unfavorable prognostic predictors for OS ( P = 0.046, P = 0.03), while only CD44 was a significant predictor for DFS ( P = 0.017). OS rate in CD133/CD44 co‐expression group was significantly lower than that in non‐co‐expression group (χ 2 = 8.44, P = 0.004). Conclusion: Our study suggested the high expression of CD133 and CD44 in the MTC, and CD133 and CD44 expressions were correlated with capsule invasion and with OS. CD133 and/or CD44 may be prognostic factors for OS and/or DFS in our MTC patients. J. Surg. Oncol. 2016;113:144–151 . © 2016 Wiley Periodicals, Inc